2019
DOI: 10.3897/phytokeys.128.35042
|View full text |Cite
|
Sign up to set email alerts
|

Isotrema sanyaense, a new species of Aristolochiaceae from Hainan, China

Abstract: Isotrema sanyaense R.T.Li, X.X.Zhu & Z.W.Wang, sp. nov., a new species from Hainan island, China, is described and illustrated here. It is morphologically most similar to I. ledongense (Han Xu, Y.D.Li & H.J.Yang) X.X.Zhu, S.Liao & J.S.Ma and I. jianfenglingense (Han Xu, Y.D.Li & H.Q.Chen) X.X.Zhu, S.Liao & J.S.Ma in the shape of leaf, flower, and the yellow to brown villous indumentum of the pedicel, ovary and calyx. However, I. sanyaense can be easily distinguished from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It can be distinguished from Aristolochia by the follow-ing set of characters: perianth strongly curved, gynostemium 3-lobed, anthers paired on the outer surface of each gynostemium segment, and capsule dehiscing basipetally (Do et al 2015a;Zhu et al 2019a). Several new species of Isotrema have been found and described from China and its neighbouring countries during recent years (Liu and Deng 2009;Xu et al 2011;Yao 2012;Huang et al 2013Huang et al , 2015Wu et al 2013Wu et al , 2015Do et al 2014Do et al , 2015aDo et al , 2015bDo et al , 2015cDo et al , 2015dDo et al , 2016Do et al , 2019Huong et al 2014;Lu and Wang 2014;Ohi-Toma et al 2014;Zhu et al 2015Zhu et al , 2016Zhu et al , 2017aZhu et al , 2017bZhu et al , 2018Zhu et al , 2019bZhu et al , 2019cGong et al 2018;Yang et al 2018;Li et al 2019;Peng et al 2019;Zhou et al 2019;Cai et al 2020aCai et al , 2020b. Currently, a total of 106 species have been reported from Isotrema, most of which are distributed in eastern and southern Asia, with some species further extended to northern and central America (Zhu et al 2019a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be distinguished from Aristolochia by the follow-ing set of characters: perianth strongly curved, gynostemium 3-lobed, anthers paired on the outer surface of each gynostemium segment, and capsule dehiscing basipetally (Do et al 2015a;Zhu et al 2019a). Several new species of Isotrema have been found and described from China and its neighbouring countries during recent years (Liu and Deng 2009;Xu et al 2011;Yao 2012;Huang et al 2013Huang et al , 2015Wu et al 2013Wu et al , 2015Do et al 2014Do et al , 2015aDo et al , 2015bDo et al , 2015cDo et al , 2015dDo et al , 2016Do et al , 2019Huong et al 2014;Lu and Wang 2014;Ohi-Toma et al 2014;Zhu et al 2015Zhu et al , 2016Zhu et al , 2017aZhu et al , 2017bZhu et al , 2018Zhu et al , 2019bZhu et al , 2019cGong et al 2018;Yang et al 2018;Li et al 2019;Peng et al 2019;Zhou et al 2019;Cai et al 2020aCai et al , 2020b. Currently, a total of 106 species have been reported from Isotrema, most of which are distributed in eastern and southern Asia, with some species further extended to northern and central America (Zhu et al 2019a).…”
mentioning
confidence: 99%
“…China accommodates ca. 66 species, among which 55 species are endemic (Huang et al 2003;Li et al 2019;Peng et al 2019;Zhou et al 2019;Zhu et al 2019aZhu et al , 2019bZhu et al , 2019cZhu et al , 2019dCai et al 2020aCai et al , 2020b.…”
mentioning
confidence: 99%
“…Currently, there are more than 70 species of Aristolochia known from China, including many new species that have been described from Yunnan, Guangxi, Guangdong, Zhejiang and Hainan in recent years (Gong et al 2018;Zhu et al 2018Zhu et al , 2019bZhu et al , 2019dLi et al 2019;Peng et al 2019;Zhou et al 2019). As one of the most biodiverse regions of China, Guangxi has 22 Aristolochia species (Peng et al 2019;Zhu et al 2019c), including A. bambusifolia C.F.Liang ex H.Q.Wen, A. longlinensis Yan Liu & L. Wu and A. gongchengensis,Y.S.Huang, Y.D.Peng & C.R.Lin, which are endemic in the region (Qin and Liu 2010;Huang et al 2015;Wu et al 2015) During a fieldwork in Yachang Orchid National Nature Reserve of north-western Guangxi, China in April 2019, we discovered a special flowering plant of Aristolochiaceae and speculated that it might be a new species of Aristolochia, based on its flower structure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain more detailed morphological data, we came back to the same location once again and collected specimens of mature capsules in July 2019. After consulting Flora of China (Hwang et al 2003) and other relevant literature (Merrill and Chun 1940;Liang 1975;Chow and Huang 1975;Hwang 1981;Cheng et al 1988;Ma 1989aMa , 1989bMa and Cheng 1989;Wen 1992;Liu and Deng 2009;Xu et al 2011;Huang et al 2013Huang et al , 2015Wu et al 2013Wu et al , 2015Do et al 2014Do et al , 2015aDo et al , 2015bDo et al , 2016Do et al , 2019Huong et al 2014;Zhu et al 2015Zhu et al , 2016Zhu et al , 2017aZhu et al , 2017bZhu et al , 2018Zhu et al , 2019bZhu et al , 2019dDo and Nghiem 2017;Gong et al 2018;Li et al 2019;Peng et al 2019;Zhou et al 2019;Cai et al 2020), as well as comparisons amongst this unknown species and its morphologically most similar species, we confirmed that this species was clearly different from the known Aristolochia species. Hence, it is here described and illustrated as a new species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one of the subgenera, Aristolochia subgen. Siphisia was reinstated to be an independent genus, Isotrema Raf., with morphological synapomorphies, such as strongly curved perianth, 3-lobed gynostemium, anthers paired on the outer surface of each gynostemium segment (Zhu et al 2019a). In China and neighbouring countries, several species belonging to Isotrema have been described in recent years (Liu and Deng 2009; Xu et al 2011; Yao 2012; Huang et al 2013, 2015; Wu et al 2013, 2015; Do et al 2014, 2015a, b, c, d, 2016, 2017, 2019; Huong et al 2014; Lu and Wang 2014; Ohi-Toma et al 2014; Zhu et al 2015, 2016, 2017a, b, 2018, 2019b; Gong et al 2018; Yang et al 2018; Li et al 2019; Peng et al 2019; Zhou et al 2019). Additionally, a useful key to Asian species of Isotrema (Aristolochia subgenus Siphisia) is provided by Do et al (2015a).…”
Section: Introductionmentioning
confidence: 99%